Structural studies of zirconia and yttria doped zirconia for analysing it phase stabilization criteria. Issue 1 (January 2021) - Kumar, Ankit; Kumar, Pravin; Dhaliwal, A S
Abstract: In this work, the target of zirconia with 2-inch diameter is prepared from the powder form having a particle size 5 µm by giving 4 tonnes of pressure in the hydraulic press. The prepared target is sintered at 1000-degree Celsius for 10 hrs. Yttria-stabilized zirconia target is also obtained in a similar process. The structural properties of both targets are investigated using Ɵ-2Ɵ geometry of X-ray diffractometer system. The changes in structure are studied in doped and undoped zirconia. The structural findings are showing the transformation of phase with doping. These studies help to understand the structural properties of zirconia with and without doping for technological application.